Knockout of family with sequence similarity 170 member A (Fam170a) causes male subfertility, while Fam170b is dispensable in mice. Issue 2 (22nd May 2020) - Devlin, Darius J; Nozawa, Kaori; Ikawa, Masahito; Matzuk, Martin M
Abstract: Families with sequence similarity 170 members A and B (FAM170A and FAM170B) are testis-specific, paralogous proteins that share 31% amino acid identity and are conserved throughout mammals. While previous in vitro experiments suggested that FAM170B, an acrosome-localized protein, plays a role in the mouse sperm acrosome reaction and fertilization, the role of FAM170A in the testis has not been explored. In this study, we used CRISPR/Cas9 to generate null alleles for each gene, and homozygous null (−/−) male mice were mated to wild-type females for 6 months to assess fertility. Fam170b −/− males were found to produce normal litter sizes and had normal sperm counts, motility, and sperm morphology. In contrast, mating experiments revealed significantly reduced litter sizes and a reduced pregnancy rate from Fam170a −/− males compared with controls. Fam170a −/− ; Fam170b −/− double knockout males also produced markedly reduced litter sizes, although not significantly different from Fam170a −/− alone, suggesting that Fam170b does not compensate for the absence of Fam170a . Fam170a −/− males exhibited abnormal spermiation, abnormal head morphology, and reduced progressive sperm motility. Thus, FAM170A has an important role in male fertility, as the loss of the protein leads to subfertility, while FAM170B is expendable. The molecular functions of FAM170A in spermatogenesis are as yet unknown; however, the protein localizes to the nucleus of elongating spermatids and may mediate its effects on spermatid head shaping and spermiation by regulating the expression of other genes. This work provides the first described role of FAM170A in reproduction and has implications for improving human male infertility diagnoses. Abstract : The testis-specific protein FAM170A plays a role in sperm head morphology and motility that is critical for fertility, while its paralog, FAM170B, is not essential.